Women and Warfare: Shifting Status in Precapitalist State Formation - Gailey, Christine Ward (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1984)
Women’s engagement in warfare has been offered as requisite to the eradication of gender hierarchy. Their presumed non-involvement in combat has been presented as an indication of lower status. Both views are critiqued in this article. In kinship societies, women’s engagement in warfare is discussed. The relationship of warfare to social authority is considered in the context of class formative, and often colonial, pressures. Warfare in precapitalist state societies is considered as one form of labor service or conscript labor. Women’s engagement or non-involvement in state-sponsored warfare is analyzed in the context of class formation and surplus extraction. Warfare is not considered to be determinant of women’s status.